2018
DOI: 10.1002/jcp.26373
|View full text |Cite
|
Sign up to set email alerts
|

TET2 expression is a potential prognostic and predictive biomarker in cytogenetically normal acute myeloid leukemia

Abstract: TET2 (Ten-Eleven Translocation 2) gene is a member of TET family that can modify DNA through catalyzing the conversion of 5-methylcytosine (5-mC) into 5-hydroxymethylcytosine (5-hmC). Although TET2 mutation has been disclosed in a variety of hematopoietic malignancies, the prognostic implication of TET2 expression in acute myeloid leukemia (AML) remains largely elusive. In this study, real-time quantitative PCR was carried out to detect the level of TET2 transcript in 134 de novo AML patients and 35 healthy do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 41 publications
3
17
1
1
Order By: Relevance
“…Decreased expression of TET2 was involved in prostate cancer progression by regulating global methylation status . Decreased expression levels of TET2 and 5‐hmC involving in the pathogenesis predicted adverse survival outcomes in AML and MDS . Experiments on two different mouse models have shown that TET2 deficiency affects the development of bone marrow and lymphoid lineage cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Decreased expression of TET2 was involved in prostate cancer progression by regulating global methylation status . Decreased expression levels of TET2 and 5‐hmC involving in the pathogenesis predicted adverse survival outcomes in AML and MDS . Experiments on two different mouse models have shown that TET2 deficiency affects the development of bone marrow and lymphoid lineage cells.…”
Section: Discussionmentioning
confidence: 99%
“…21 Decreased expression levels of TET2 and 5-hmC involving in the pathogenesis predicted adverse survival outcomes in AML and MDS. 9,14 Experiments on two different mouse models have shown that TET2 deficiency affects the development of bone marrow and lymphoid lineage cells. It is suggested that the injury of TET2 function or expression can also lead to the occurrence of hemolymphatic tumor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed TET2 expression and 5-hmC levels were found also decreased in pediatric MDS cases, a population known to be rarely mutated in TET2 gene [41]. TET2 expression levels have also been identified as a predictive and a prognostic biomarker in cytogenetically normal (CN)-AML [42]. Indeed, low TET2 expression had a negative impact on overall survival (OS) in both non-M3 and CN-AML (p = 0.016 and 0.044, respectively), although multivariable analysis confirmed these results only for the CN group [42].…”
Section: Tet2: a Pivotal Gene In Myeloid Malignanciesmentioning
confidence: 99%
“…TET2 mutations are associated with an increased risk of MDS progression and confer a poor prognosis in AML [13,119]. Low TET2 mRNA levels are related to poor prognosis and TET2 mRNA levels might be a potential prognostic biomarker for AML since levels increase upon remission and decrease upon relapse [122].…”
Section: Epigenetic Changes In Age-related Haematopoietic Malignanmentioning
confidence: 99%